Copper incorporated titanium dioxide phtotcatalyst for hydrogen production - Xu, Shiping (2012)
This thesis aims to explore the potential of cost-effective Cu-TiO2 in photocatalytic H2 production by fabricating highly efficient Cu-TiO2 photocatalyst and employing optimal operation conditions. Effect of operation conditions on H2 generation over Cu-TiO2 photocatalyst was firstly investigated to determine the optimal operation conditions. Effect of fabrication method was then studied, and found that various fabrication methods led to different chemical states of Cu, as well as different distribution ratio of Cu between surface and bulk phases. Both factors were proved to influence photocatalytic H2 generation. Activity of Cu-TiO2 could be further improved by employing TiO2 nanotube as TiO2 support, where the high activity was mainly attributed to the unique one-dimensional tubular structure, large BET surface area and high dispersion of Cu component. In addition, simultaneous Cu2+ removal and H2 production were proved to be feasible over TiO2 nanotube, which is interesting to achieve wastewater treatment with H2 production concurrently.